Relationships of Corporate Governance Mechanisms and Financial Performance in Islamic Banks: A Meta-Analysis - Li , Yongqiang; Armstrong , Anona; Clarke , Andrew (Journal of Law and Governance, 2014)
Relationships between corporate governance mechanisms and the financial performance of Islamic banks have been researched extensively in prior empirical research. However, the results are mixed, mainly due to the heterogeneity of the samples used for the empirical investigations. This paper reports the results of a meta-analysis of the existing literature on governance mechanisms from which a framework was developed to guide the constructions of governance indices. The results showed that Islamic banks banks tend to have better financial performance if there was (1) a higher proportion of independent directors on the board; (2) the Shari”ah Supervisory Board was large and consisted of top scholars; (3)numerous directors; (4) the CEO was chairman; (5) auditing was enforced and (6) ownership structure was dispersed, reducing shareholding of directors, foreigners and institutional investors, while increasing family and governments’ shareholding. Managers’ shareholding was insignificant.